Clinical significance of IgA nephropathy with hyperuricemia - Han Zhou; Wei Liang; Guo-hua Ding (Linchuang shenzangbing zazhi, 2024)
As one of the most common primary glomerulopathies, immunoglobulin A nephropathy（IgAN） is a major cause of end-stage renal disease （ESRD）. Its proper treatment has remained rather challenging. Disease progression may be delayed if associated risk factors are intervened. Hyperuricemia is a common clinical feature of IgAN and it is correlated with disease progression. However, the relationship has been elusive between hyperuricemia, pathological injury and disease progression in IgAN. This review focused upon the prevalence of hyperuricemia in IgAN, related pathogenesis and the relationship with the progression of IgAN and therapeutic targets.